Evaluation of solid and submerged fermentations for the production of cyclodextrin glycosyltransferase by Paenibacillus campinasensis H69-3 and characterization of crude enzyme - Alves-Prado, Heloiza Ferreira [UNESP]; Gomes, Eleni [UNESP]; Da Silva, Roberto [UNESP] (Springer Nature, 2006)
Cyclodextrin glycosyltransferase (CGTase) is an enzyme that produces cyclodextrins from starch by an intramolecular transglycosylation reaction. Cyclodextrins have been shown to have a number of applications in the food, cosmetic, pharmaceutical, and chemical industries. In the current study, the production of CGTase by Paenibacillus campinasensis strain H69-3 was examined in submerged and solid-state fermentations. P. campinasensis strain H69-3 was isolated from the soil, which grows at 45°C, and is a Gram-variable bacterium. Different substrate sources such as wheat bran, soybean bran, soybean extract, cassava solid residue, cassava starch, corn starch, and other combinations were used in the enzyme production. CGTase activity was highest in submerged fermentations with the greatest production observed at 48-72 h. The physical and chemical properties of CGTase were determined from the crude enzyme produced from submerged fermentations. The optimum temperature was found to be 70-75°C, and the activity was stable at 55°C for 1 h. The enzyme displayed two optimum pH values, 5.5 and 9.0 and was found to be stable between a pH of 4.5 and 11.0. Copyright © 2006 by Humana Press Inc. All rights of any nature whatsoever reserved.
Keywords: Cyclodextrin glycosyltransferase; Paenibacillus campinasensis; Solid-state fermentation; Submerged fermentation